We Need Two Worlds' Chinese Immigrant Associations in a Western Society - Minghuan, Li (Amsterdam University Press, 1999)
A highly informative report on Chinese immigrants in the Netherlands, We Need Two Worlds is a clear and well-structured dissertation which presents a considerable amount of new material to existing knowledge of Chinese associations and their role in the Netherlands. The situation in Amsterdam is comparable to Chinese societies in other major cities, e.g. New York and London. This comprehensive study will help Western students, academics, civil servants, politicians and journalists who have an interest in Chinese culture to gain a better understanding of the significance of their associations. It also illustrates how Chinese immigrants live together and operate within a western society.